STEM Cooperating Teachers' Professional Growth: The Positive Impacts of a Year-Long Clinical Residency Collaboration - Kimberly M. Baker; Katherine W. Stickney; Deborah D. Sachs (MDPI AG, 2024)
Teacher residency programs integrate coursework with clinical practice in a year-long residency in which pre-service teachers work under the guidance of a cooperating teacher who has demonstrated excellence in teaching and mentoring. The purpose of this study was to examine the reasons for serving as a cooperating teacher and investigate how clinical residency pre-service teachers promote growth in the professional practice of cooperating teachers as teachers and teacher leaders. In this longitudinal qualitative study, we gathered data through semi-structured interviews and responses to survey questions over a five-year period. Ten STEM cooperating teachers (six female and four male) with 7 to 18 years of full-time teaching experience in biology, chemistry, or mathematics participated. A thematic analysis was used to analyze the interview transcripts and survey responses. The primary motivation for serving as a cooperating teacher was the desire to share experiences and support new teachers. Cooperating teachers described the following benefits: increased self-reflection and continuing reflective practice; meaningful collaboration with pre-service teachers; learned new teaching strategies to enrich their own teaching practice; improved communication skills; and the impetus to become teacher leaders. These findings support that clinical residency teaching programs are beneficial for STEM cooperating teachers and promote their professional growth.